Antibacterial composite non-woven fabric
By adopting a composite structure of wear-resistant layer, liner layer and antibacterial layer in composite nonwoven fabrics, combined with hot pressing technology, the problems of poor antibacterial, wear-resistant and heat-resistant properties of existing nonwoven fabrics have been solved, and better performance has been achieved.
Patent Information
- Application Number
- CN202411991784.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-12-31
AI Technical Summary
The antibacterial, wear-resistant and heat-resistant properties of existing composite non-woven fabrics are poor, making it difficult to meet the needs of medical, hygiene, home and industry.
An antibacterial composite nonwoven fabric is prepared by hot press bonding using a composite structure including a wear-resistant layer, a liner layer and an antibacterial layer. The antibacterial layer material is made of composite antibacterial agent and polyacrylic acid, the wear-resistant layer material is made of specific chemical substances, and the inner lining layer is composed of spunbonded nonwoven fabric.
The antibacterial, wear and heat resistance of non-woven fabrics is significantly improved, so that they can show excellent performance in practical applications.
Smart Images

Figure BDA0005223806910000031 
Figure BDA0005223806910000051 
Figure BDA0005223806910000161
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of non-woven fabric preparation, and specifically relates to an antibacterial composite non-woven fabric. Background Art
[0002] In recent years, with the significant improvement of global health awareness and people's increasing requirements for quality of life, the application scope of antibacterial materials has become increasingly wide. In particular, the demand for antibacterial non-woven fabrics in the fields of medical, hygiene, home and industry has continued to grow, promoting the rapid development of antibacterial composite non-woven fabric technology.
[0003] Traditional non-woven fabrics often lack effective antibacterial mechanisms and are difficult to effectively inhibit or kill bacteria, viruses and other microorganisms, which not only affects the service life and performance of non-woven fabrics, but may also pose a potential threat to people's health. In addition, traditional composite non-woven fabrics are relatively loose in fiber structure and are easily worn or damaged by external forces, thereby reducing the service life and performance of non-woven fabrics. Especially in some fields with high requirements for wear resistance, such as industrial packaging, outdoor products, etc., the wear resistance of traditional composite non-woven fabrics often cannot meet the needs.
[0004] Patent CN105398152A discloses an antibacterial composite non-woven fabric, which includes, from bottom to top, an antibacterial non-woven fabric, an antibacterial mesh cloth layer and a hydrophilic layer; the antibacterial non-woven fabric is made of antibacterial acrylic fiber, which is prepared by modification with nano-titanium dioxide, chitin and copper sulfate; the antibacterial mesh cloth layer is prepared by weaving textile fibers and silver fibers in a mass ratio of 100:1, and then composited with the antibacterial non-woven fabric by a hydroentanglement method, and has antibacterial and hydrophilic properties, but the antibacterial properties, wear resistance and heat resistance of the non-woven fabric prepared by this method still have room for improvement. Summary of the invention
[0005] The object of the present invention is to provide an antibacterial composite nonwoven fabric, which is used to solve the technical problem that the composite nonwoven fabric in the prior art has poor antibacterial performance, wear resistance and heat resistance.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] The invention provides an antibacterial composite non-woven fabric, comprising a wear-resistant layer, an inner lining layer and an antibacterial layer, wherein the inner lining layer is located between the wear-resistant layer and the antibacterial layer, the layers are bonded by hot pressing, the antibacterial layer material is prepared from a composite antibacterial agent and polyacrylic acid, the inner lining layer material is composed of a spunbonded non-woven fabric, and the wear-resistant layer material is prepared from 4-aminophenol, 2-chloro-5-nitrotrifluorotoluene, 4-nitrobenzoyl chloride, hydrazine hydrate and 3,4,9,10-perylenetetracarboxylic dianhydride.
[0008] Preferably, the method for preparing the composite antibacterial agent comprises the following steps:
[0009] Q1: 3-phenyl-2-acryloyl chloride and ethanolamine hydrochloride are added to a container filled with nitrogen and equipped with a condensing device, and then hydroquinone is added, the temperature is raised to react, vigorously stirred, then the temperature is lowered to react, cooled, diluted, precipitated, washed, dried, recrystallized, and dried to obtain monomer 1;
[0010] Q2: Monomer 1 and butyl methacrylate are added to a container equipped with a magnetic stirrer, nitrogen is introduced, dimethyl sulfoxide is added, the temperature is raised, azobisisobutyronitrile is dissolved in dimethyl sulfoxide and then slowly added dropwise to the container, react, precipitate, wash, redissolve, precipitate, wash, and dry to obtain monomer 2;
[0011] Q3: Add monomer 2, trimethylamine and 1H-pyrazole-1-carboximidamide hydrochloride to a container containing deionized water, introduce nitrogen, and react at room temperature. After the reaction is completed, dialyze, concentrate by rotary evaporation, and freeze-dry to obtain a composite antibacterial agent.
[0012] In the above process, 3-phenyl-2-acryloyl chloride and ethanolamine hydrochloride are first reacted to obtain monomer 1, and then monomer 1 is polymerized with butyl methacrylate to obtain monomer 2, and then a composite antibacterial agent is obtained through a guanidation reaction, wherein the synthetic reaction formula of the composite antibacterial agent is as follows:
[0013]
[0014] The results of mass spectrometry analysis of monomer 1 were: m / z: 227.07 (100.0%), 229.07 (32.0%), 228.07 (12.3%), 230.07 (4.0%), 229.08 (1.1%).
[0015] Preferably, in Q1, the molar ratio of 3-phenyl-2-acryloyl chloride to ethanolamine hydrochloride is (3-3.5): (2-2.3), the heating reaction temperature is 90-95°C, the reaction time is 1-2h, the cooling reaction temperature is 70-75°C, the reaction time is 2-4h, cooled to 25-30°C, diluted with tetrahydrofuran, precipitated with n-pentane, washed with distilled water, and recrystallized with a mixed solution of ethyl acetate and isopropanol in a volume ratio of 7:3.
[0016] Preferably, in Q2, the amount ratio of monomer 1, butyl methacrylate, dimethyl sulfoxide, azobisisobutyronitrile and dimethyl sulfoxide in which azobisisobutyronitrile is dissolved is (1-1.8) g: (2-2.4) g: (15-20) mL: (0.04-0.07) g: (3-5) mL, the heating temperature is 70-75°C, the reaction time is 12-16 h, precipitated with acetone, washed, redissolved with dimethyl sulfoxide, precipitated with acetone again, washed, and the drying temperature is 40-45°C; in Q3, the amount ratio of monomer 2, trimethylamine and 1H-pyrazole-1-carboxamidine hydrochloride is (1-1.3) g: (3-3.8) g: (1.5-1.95) g, the reaction time at room temperature is 20-24 h, the molecular weight cutoff of the dialysis bag is 1000, and the dialysis time is 48-56 h.
[0017] Preferably, the method for preparing the wear-resistant layer material comprises the following steps:
[0018] S1: Add 4-aminophenol, 2-chloro-5-nitrotrifluorotoluene and potassium carbonate to a container filled with N,N-dimethylformamide, heat up to react, cool down after the reaction, add distilled water, stir, collect the crude product, recrystallize, and obtain intermediate product 1; add 4-nitrobenzoyl chloride to a container filled with tetrahydrofuran, stir until completely dissolved, drop pyridine, react, then dissolve intermediate product 1 in tetrahydrofuran and slowly drop it into the container, stir under ice bath, heat up to react, cool, pour into distilled water, filter, recrystallize, filter to obtain intermediate product 2;
[0019] S2: Under nitrogen atmosphere, add intermediate product 2 to a container filled with ethanol, stir, then add palladium activated carbon, heat to react, then add hydrazine hydrate dropwise, keep warm and reflux to react, after the reaction is completed, filter and collect the filtrate while hot, rotary evaporate to obtain a crude product, and recrystallize to obtain intermediate 3;
[0020] S3: Add the intermediate 3 to a container containing N,N-dimethylacetamide, stir and dissolve, then add 3,4,9,10-perylenetetracarboxylic dianhydride, stir, mix and react at room temperature under a nitrogen environment, spread, heat, heat and cure, and cool to obtain a wear-resistant layer material.
[0021] In the above process, the synthetic reaction formula of the wear-resistant layer material is as follows:
[0022]
[0023] The results of mass spectrometry analysis of intermediate product 1 are: m / z: 298.06 (100.0%), 299.06 (14.3%), 300.06 (1.7%); the results of mass spectrometry analysis of intermediate product 2 are: m / z: 447.07 (100.0%), 448.07 (22.0%), 449.07 (3.7%), 448.06 (1.1%); the results of mass spectrometry analysis of intermediate product 3 are: m / z: 387.12 (100.0%), 388.12 (22.8%), 389.13 (2.3%).
[0024] Preferably, in S1, the molar ratio of 4-aminophenol, 2-chloro-5-nitrotrifluorotoluene and potassium carbonate is (0.09-0.12): (0.09-0.11): (0.068-0.073), the temperature of the reaction is 80-90°C, the reaction time is 10-12h, and recrystallization is performed using ethanol; the molar ratio of 4-nitrobenzoyl chloride, pyridine and intermediate 1 is (0.01-0.015): (0.018-0.026): (0.017-0.025), the reaction time is 30-45min, the stirring time under ice bath is 3-5h, the temperature of the reaction is 60-80°C, the time is 10-12h, and recrystallization is performed using N,N-dimethylformamide.
[0025] Preferably, in S2, the dosage ratio of the intermediate product 2, ethanol, palladium activated carbon and hydrazine hydrate is (4.47-5.82) g: (150-175) mL: (0.18-0.21) g: (25-35) mL, the stirring time is 2-4 h, the heating reaction temperature is 70-75°C, the reaction time is 1-2 h, the insulation reflux reaction temperature is 70-75°C, the reaction time is 12-14 h, and recrystallization is carried out with ethanol.
[0026] Preferably, in S3, the amount ratio of intermediate 3, N,N-dimethylacetamide and 3,4,9,10-perylenetetracarboxylic dianhydride is (8-12) g: (15-25) mL: (6-8) g, the mixing reaction time at room temperature is 10-14 h, the heating temperature is 80-85°C, the time is 5-7 h, and the temperature rise curing process is: reaction at 100°C for 2 h, reaction at 150°C for 1 h, reaction at 200°C for 1 h, reaction at 250°C for 1 h, and reaction at 300°C for 1 h.
[0027] Preferably, the method for preparing the antibacterial composite nonwoven fabric comprises the following steps:
[0028] Step 1: Mix the composite antibacterial agent and polyacrylic acid, and then perform electrospinning to obtain an antibacterial layer material;
[0029] Step 2: placing the spunbond nonwoven fabric between the antibacterial layer material and the wear-resistant layer material, preheating, hot pressing, cooling and shaping, and cutting to obtain the antibacterial composite nonwoven fabric.
[0030] Preferably, in step 1, the usage ratio of the composite antibacterial agent to polyacrylic acid is (3-6) g: (60-90) g.
[0031] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:
[0032] 1. The present invention first uses 3-phenyl-2-acryloyl chloride, ethanolamine hydrochloride, butyl methacrylate and 1H-pyrazole-1-carboxamidine hydrochloride as raw materials to prepare a composite antibacterial agent, and composites the composite antibacterial agent with polyacrylic acid to obtain an antibacterial layer material, and then uses 4-aminophenol, 2-chloro-5-nitrotrifluorotoluene, 4-nitrobenzoyl chloride, hydrazine hydrate and 3,4,9,10-perylenetetracarboxylic dianhydride as raw materials to prepare a wear-resistant layer material, and composites the antibacterial layer material, the wear-resistant layer material and the lining layer to obtain a composite non-woven fabric with excellent antibacterial performance, wear resistance and heat resistance.
[0033] 2. The present invention adds the prepared composite antibacterial agent to the non-woven fabric, which can effectively improve its antibacterial performance. The guanidine group contained in the composite antibacterial agent has a positive charge, which can interact with the negative charge on the cell membrane to destroy the integrity of the cell membrane, thereby causing the bacterial contents to flow out and quickly killing the bacteria. The composite antibacterial agent can enter the bacterial cells and interfere with their metabolic process. By inhibiting the synthesis of bacterial DNA or RNA and interfering with protein synthesis, the growth and reproduction of bacteria are inhibited. At the same time, the composite antibacterial agent is tightly combined with polyacrylic acid to form a stable antibacterial layer material, which maintains its antibacterial effect for a long time and is not easily destroyed by the external environment.
[0034] 3. The present invention applies the prepared wear-resistant layer material to non-woven fabrics, which can effectively improve the wear resistance and heat resistance of the non-woven fabrics. The wear-resistant layer material contains high-energy amide bonds and imide bonds, which ensure that it is not easy to break when heated. The introduction of aromatic diamines not only increases the rigidity of the wear-resistant layer material, but also further significantly improves the heat resistance. At the same time, the high melting point and stable conjugated system of the 3,4,9,10-perylenetetracarboxylic dianhydride used also enhance the thermal stability of the wear-resistant layer material. In addition, the alternating arrangement of amide bonds and imide bonds will form a cross-linked structure, which limits the molecular chain movement of the wear-resistant layer material, reduces the movement of chain segments during thermal decomposition, and further improves the heat resistance. The cross-linked structure formed by the wear-resistant layer material effectively improves its tear strength, enables it to resist damage from external forces, and improves its wear resistance. DETAILED DESCRIPTION
[0035] The following will be described clearly and completely in conjunction with the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] Example 1: This example discloses a method for preparing a composite antibacterial agent, comprising the following steps:
[0037] Q1: 2.71 g of 3-phenyl-2-acryloyl chloride and 1.05 g of ethanolamine hydrochloride were added to a container filled with nitrogen and equipped with a condensing device, and then 0.012 g of hydroquinone was added, and the temperature was raised to 95°C for reaction for 2 h, and stirred vigorously, and then the temperature was lowered to 75°C for reaction for 4 h, and then cooled to 25°C, diluted with tetrahydrofuran, precipitated with n-pentane, washed with distilled water, dried, and recrystallized with a mixed solution of ethyl acetate and isopropanol in a volume ratio of 7:3, and dried to obtain monomer 1;
[0038] Q2: 1.4 g of monomer 1 and 2.2 g of butyl methacrylate were added to a container equipped with a magnetic stirrer, nitrogen was introduced, and then 17.5 mL of dimethyl sulfoxide was added, and the temperature was raised to 75°C. 0.055 g of azobisisobutyronitrile was dissolved in 4 mL of dimethyl sulfoxide and then slowly added dropwise to the container, and the reaction was carried out for 14 hours. The mixture was precipitated with acetone, washed, redissolved with dimethyl sulfoxide, precipitated again with acetone, washed, and dried at 45°C to obtain monomer 2;
[0039] Q3: 1.15 g of monomer 2, 3.4 g of trimethylamine and 1.67 g of 1H-pyrazole-1-carboximidamide hydrochloride were added to a container containing 60 mL of deionized water. After nitrogen was introduced, the mixture was reacted at room temperature for 24 h. After the reaction was completed, the mixture was dialyzed for 48 h using a dialysis bag with a molecular weight cutoff of 1000. The mixture was concentrated by rotary evaporation and freeze-dried to obtain a composite antibacterial agent.
[0040] This embodiment discloses a method for preparing a wear-resistant layer material, comprising the following steps:
[0041] S1: 11.45 g 4-aminophenol, 22.56 g 2-chloro-5-nitrotrifluorotoluene and 9.72 g potassium carbonate were added to a container containing 60 mL N, N-dimethylformamide, and the temperature was raised to 80°C for reaction for 12 h. After the reaction was completed, the temperature was lowered, distilled water was added, stirred, the crude product was collected, and recrystallized from ethanol to obtain intermediate product 1; 2.32 g 4-nitrobenzoyl chloride was added to a container containing 30 mL tetrahydrofuran, stirred until completely dissolved, 1.738 g pyridine was added dropwise, and the reaction was carried out for 45 min. Then 6.258 g of intermediate product 1 was dissolved in 30 mL tetrahydrofuran and slowly added dropwise to the container, stirred under an ice bath for 5 h, and the temperature was raised to 80°C for reaction for 12 h. The mixture was cooled, poured into distilled water, filtered, and recrystallized from N, N-dimethylformamide. The intermediate product 2 was filtered and obtained;
[0042] S2: Under nitrogen atmosphere, 5.31 g of intermediate product 2 was added to a container containing 157.5 mL of ethanol, stirred for 3 h, then 0.2 g of palladium activated carbon was added, the temperature was raised to 75 °C for reaction for 2 h, then 30 mL of hydrazine hydrate was added dropwise, and the temperature was kept at 75 °C for reflux reaction for 12 h. After the reaction was completed, the filtrate was collected by hot filtration and rotary evaporation to obtain a crude product, which was recrystallized from ethanol to obtain intermediate 3;
[0043] S3: Add 10g of intermediate 3 to a container containing 20mL of N,N-dimethylacetamide, stir to dissolve, then add 7g of 3,4,9,10-perylenetetracarboxylic dianhydride, stir, mix and react at room temperature for 12h under nitrogen environment, spread flat, heat at 85℃ for 5h, and heat to cure. The process is: react at 100℃ for 2h, react at 150℃ for 1h, react at 200℃ for 1h, react at 250℃ for 1h, react at 300℃ for 1h, cool, and obtain the wear-resistant layer material.
[0044] This embodiment discloses a method for preparing an antibacterial composite nonwoven fabric, comprising the following steps:
[0045] Step 1: 4.5 g of the composite antibacterial agent and 75 g of polyacrylic acid are mixed, and then electrospinned to obtain an antibacterial layer material;
[0046] Step 2: placing the spunbond nonwoven fabric between the antibacterial layer material and the wear-resistant layer material, preheating, hot pressing, cooling and shaping, and cutting to obtain the antibacterial composite nonwoven fabric.
[0047] Example 2: This example discloses a method for preparing a composite antibacterial agent, comprising the following steps:
[0048] Q1: 2.499 g of 3-phenyl-2-acryloyl chloride and 0.975 g of ethanolamine hydrochloride were added to a container filled with nitrogen and equipped with a condensing device, and then 0.012 g of hydroquinone was added, the temperature was raised to 95°C for reaction for 2 h, and the mixture was stirred vigorously. The temperature was then lowered to 75°C for reaction for 4 h, and the mixture was cooled to 25°C, diluted with tetrahydrofuran, precipitated with n-pentane, washed with distilled water, dried, and recrystallized with a mixed solution of ethyl acetate and isopropanol in a volume ratio of 7:3, and dried to obtain monomer 1;
[0049] Q2: 1.8 g of monomer 1 and 2.4 g of butyl methacrylate were added to a container equipped with a magnetic stirrer, nitrogen was introduced, and then 15 mL of dimethyl sulfoxide was added, and the temperature was raised to 75°C. 0.04 g of azobisisobutyronitrile was dissolved in 5 mL of dimethyl sulfoxide and then slowly added dropwise to the container, and the reaction was carried out for 14 hours. The mixture was precipitated with acetone, washed, redissolved with dimethyl sulfoxide, precipitated again with acetone, washed, and dried at 45°C to obtain monomer 2;
[0050] Q3: 1.3 g of monomer 2, 3.8 g of trimethylamine and 1.95 g of 1H-pyrazole-1-carboximidamide hydrochloride were added to a container containing 60 mL of deionized water. After nitrogen was introduced, the mixture was reacted at room temperature for 24 h. After the reaction was completed, the mixture was dialyzed for 48 h using a dialysis bag with a molecular weight cutoff of 1000. The mixture was concentrated by rotary evaporation and freeze-dried to obtain a composite antibacterial agent.
[0051] This embodiment discloses a method for preparing a wear-resistant layer material, comprising the following steps:
[0052] S1: 9.81 g of 4-aminophenol, 20.304 g of 2-chloro-5-nitrotrifluorotoluene and 9.38 g of potassium carbonate were added to a container containing 60 mL of N,N-dimethylformamide, and the temperature was raised to 80°C for reaction for 12 h. After the reaction was completed, the temperature was lowered, distilled water was added, and the mixture was stirred. The crude product was collected and recrystallized from ethanol to obtain intermediate product 1; 2.784 g of 4-nitrobenzoyl chloride was added to a container containing 30 mL of tetrahydrofuran, and the mixture was stirred until completely dissolved. 1.422 g of pyridine was added dropwise and the reaction was carried out for 45 min. Then, 5.066 g of intermediate product 1 was dissolved in 30 mL of tetrahydrofuran and the mixture was slowly added dropwise to the container, and the mixture was stirred under an ice bath for 5 h. The mixture was heated to 80°C for reaction for 12 h, cooled, poured into distilled water, filtered, and recrystallized from N,N-dimethylformamide. The intermediate product 2 was filtered and obtained;
[0053] S2: Under nitrogen atmosphere, 4.47 g of intermediate product 2 was added to a container containing 150 mL of ethanol, stirred for 3 h, then 0.18 g of palladium activated carbon was added, the temperature was raised to 75 °C for reaction for 2 h, then 25 mL of hydrazine hydrate was added dropwise, and the temperature was kept at 75 °C for reflux reaction for 12 h. After the reaction was completed, the filtrate was collected by hot filtration and rotary evaporation to obtain a crude product, which was recrystallized from ethanol to obtain intermediate 3;
[0054] S3: Add 8 g of intermediate 3 to a container containing 15 mL of N,N-dimethylacetamide, stir to dissolve, then add 8 g of 3,4,9,10-perylenetetracarboxylic dianhydride, stir, mix and react at room temperature for 12 h under a nitrogen environment, spread flat, heat at 85°C for 5 h, and heat to cure. The process is: react at 100°C for 2 h, react at 150°C for 1 h, react at 200°C for 1 h, react at 250°C for 1 h, react at 300°C for 1 h, cool, and obtain a wear-resistant layer material.
[0055] This embodiment discloses a method for preparing an antibacterial composite nonwoven fabric, comprising the following steps:
[0056] Step 1: 3 g of the composite antibacterial agent and 60 g of polyacrylic acid are mixed, and then electrospinned to obtain an antibacterial layer material;
[0057] Step 2: placing the spunbond nonwoven fabric between the antibacterial layer material and the wear-resistant layer material, preheating, hot pressing, cooling and shaping, and cutting to obtain the antibacterial composite nonwoven fabric.
[0058] Example 3: This example discloses a method for preparing a composite antibacterial agent, comprising the following steps:
[0059] Q1: 2.92 g of 3-phenyl-2-acryloyl chloride and 1.12 g of ethanolamine hydrochloride were added to a container filled with nitrogen and equipped with a condensing device, and then 0.012 g of hydroquinone was added, and the temperature was raised to 95°C for reaction for 2 h, and stirred vigorously, and then the temperature was lowered to 75°C for reaction for 4 h, and then cooled to 25°C, diluted with tetrahydrofuran, precipitated with n-pentane, washed with distilled water, dried, and recrystallized with a mixed solution of ethyl acetate and isopropanol in a volume ratio of 7:3, and dried to obtain monomer 1;
[0060] Q2: 1 g of monomer 1 and 2 g of butyl methacrylate were added to a container equipped with a magnetic stirrer, nitrogen was introduced, and then 20 mL of dimethyl sulfoxide was added, and the temperature was raised to 75°C. 0.07 g of azobisisobutyronitrile was dissolved in 3 mL of dimethyl sulfoxide and then slowly added dropwise to the container, and the reaction was carried out for 14 hours. The mixture was precipitated with acetone, washed, redissolved with dimethyl sulfoxide, precipitated again with acetone, washed, and dried at 45°C to obtain monomer 2;
[0061] Q3: Add 1g monomer 2, 3g trimethylamine and 1.5g 1H-pyrazole-1-carboximidamide hydrochloride into a container containing 60mL deionized water, introduce nitrogen, and react at room temperature for 24h. After the reaction, dialyze using a dialysis bag with a molecular weight cutoff of 1000 for 48h, concentrate by rotary evaporation, and freeze-dry to obtain a composite antibacterial agent.
[0062] This embodiment discloses a method for preparing a wear-resistant layer material, comprising the following steps:
[0063] S1: 13.08 g of 4-aminophenol, 24.82 g of 2-chloro-5-nitrotrifluorotoluene and 10.07 g of potassium carbonate were added to a container containing 60 mL of N,N-dimethylformamide, and the temperature was raised to 80°C for reaction for 12 h. After the reaction was completed, the temperature was lowered, distilled water was added, and the mixture was stirred. The crude product was collected and recrystallized from ethanol to obtain intermediate product 1; 1.856 g of 4-nitrobenzoyl chloride was added to a container containing 30 mL of tetrahydrofuran, and the mixture was stirred until completely dissolved. 2.054 g of pyridine was added dropwise and the reaction was carried out for 45 min. Then, 7.45 g of intermediate product 1 was dissolved in 30 mL of tetrahydrofuran and the mixture was slowly added dropwise to the container, and the mixture was stirred under an ice bath for 5 h. The mixture was heated to 80°C for reaction for 12 h, cooled, poured into distilled water, filtered, and recrystallized from N,N-dimethylformamide. The intermediate product 2 was filtered and obtained;
[0064] S2: Under nitrogen atmosphere, 5.82 g of intermediate product 2 was added to a container containing 175 mL of ethanol, stirred for 3 h, then 0.21 g of palladium activated carbon was added, the temperature was raised to 75 °C for reaction for 2 h, then 35 mL of hydrazine hydrate was added dropwise, and the temperature was kept at 75 °C for reflux reaction for 12 h. After the reaction was completed, the filtrate was collected by hot filtration and rotary evaporation to obtain a crude product, which was recrystallized from ethanol to obtain intermediate 3;
[0065] S3: Add 12g of intermediate 3 to a container containing 25mL of N,N-dimethylacetamide, stir to dissolve, add 6g of 3,4,9,10-perylenetetracarboxylic dianhydride, stir, mix and react at room temperature for 12h under nitrogen environment, spread flat, heat at 85℃ for 5h, and heat to cure. The process is: react at 100℃ for 2h, react at 150℃ for 1h, react at 200℃ for 1h, react at 250℃ for 1h, react at 300℃ for 1h, cool, and obtain the wear-resistant layer material.
[0066] This embodiment discloses a method for preparing an antibacterial composite nonwoven fabric, comprising the following steps:
[0067] Step 1: 6 g of the composite antibacterial agent and 90 g of polyacrylic acid are mixed, and then electrospinned to obtain an antibacterial layer material;
[0068] Step 2: placing the spunbond nonwoven fabric between the antibacterial layer material and the wear-resistant layer material, preheating, hot pressing, cooling and shaping, and cutting to obtain the antibacterial composite nonwoven fabric.
[0069] Example 4: This example discloses a method for preparing a composite antibacterial agent, comprising the following steps:
[0070] Q1: 2.63 g of 3-phenyl-2-acryloyl chloride and 0.99 g of ethanolamine hydrochloride were added to a container filled with nitrogen and equipped with a condensing device, and then 0.012 g of hydroquinone was added, and the temperature was raised to 95°C for reaction for 2 h, and stirred vigorously, and then the temperature was lowered to 75°C for reaction for 4 h, and then cooled to 25°C, diluted with tetrahydrofuran, precipitated with n-pentane, washed with distilled water, dried, and recrystallized with a mixed solution of ethyl acetate and isopropanol in a volume ratio of 7:3, and dried to obtain monomer 1;
[0071] Q2: 1.2 g of monomer 1 and 2.1 g of butyl methacrylate were added to a container equipped with a magnetic stirrer, nitrogen was introduced, and then 16 mL of dimethyl sulfoxide was added, and the temperature was raised to 75°C. 0.05 g of azobisisobutyronitrile was dissolved in 3.5 mL of dimethyl sulfoxide and then slowly added dropwise to the container, and the reaction was carried out for 14 hours. The mixture was precipitated with acetone, washed, redissolved with dimethyl sulfoxide, precipitated again with acetone, washed, and dried at 45°C to obtain monomer 2;
[0072] Q3: Add 1.1g monomer 2, 3.2g trimethylamine and 1.63g 1H-pyrazole-1-carboximidamide hydrochloride into a container containing 60mL deionized water, introduce nitrogen, and react at room temperature for 24h. After the reaction, dialyze using a dialysis bag with a molecular weight cutoff of 1000 for 48h, concentrate by rotary evaporation, and freeze-dry to obtain a composite antibacterial agent.
[0073] This embodiment discloses a method for preparing a wear-resistant layer material, comprising the following steps:
[0074] S1: 10.12 g of 4-aminophenol, 21.17 g of 2-chloro-5-nitrotrifluorotoluene and 9.53 g of potassium carbonate were added to a container containing 60 mL of N,N-dimethylformamide, and the temperature was raised to 80°C for reaction for 12 h. After the reaction was completed, the temperature was lowered, distilled water was added, and the mixture was stirred. The crude product was collected and recrystallized from ethanol to obtain intermediate product 1; 2.513 g of 4-nitrobenzoyl chloride was added to a container containing 30 mL of tetrahydrofuran, and the mixture was stirred until completely dissolved. 1.601 g of pyridine was added dropwise and the reaction was carried out for 45 min. Then, 5.579 g of intermediate product 1 was dissolved in 30 mL of tetrahydrofuran and the mixture was slowly added dropwise to the container, and the mixture was stirred under an ice bath for 5 h. The mixture was heated to 80°C for reaction for 12 h, cooled, poured into distilled water, filtered, and recrystallized from N,N-dimethylformamide. The intermediate product 2 was filtered and obtained;
[0075] S2: Under nitrogen atmosphere, 4.93 g of intermediate product 2 was added to a container containing 160 mL of ethanol, stirred for 3 h, then 0.19 g of palladium activated carbon was added, the temperature was raised to 75 °C for reaction for 2 h, then 27 mL of hydrazine hydrate was added dropwise, and the temperature was kept at 75 °C for reflux reaction for 12 h. After the reaction was completed, the filtrate was collected by hot filtration and rotary evaporation to obtain a crude product, which was recrystallized from ethanol to obtain intermediate 3;
[0076] S3: Add 9 g of intermediate 3 to a container containing 17 mL of N,N-dimethylacetamide, stir to dissolve, then add 6.5 g of 3,4,9,10-perylenetetracarboxylic dianhydride, stir, mix and react at room temperature for 12 h under a nitrogen environment, spread flat, heat at 85°C for 5 h, and heat to cure. The process is: react at 100°C for 2 h, react at 150°C for 1 h, react at 200°C for 1 h, react at 250°C for 1 h, react at 300°C for 1 h, cool, and obtain a wear-resistant layer material.
[0077] This embodiment discloses a method for preparing an antibacterial composite nonwoven fabric, comprising the following steps:
[0078] Step 1: 4 g of the composite antibacterial agent and 70 g of polyacrylic acid are mixed, and then electrospinned to obtain an antibacterial layer material;
[0079] Step 2: placing the spunbond nonwoven fabric between the antibacterial layer material and the wear-resistant layer material, preheating, hot pressing, cooling and shaping, and cutting to obtain the antibacterial composite nonwoven fabric.
[0080] Example 5: This example discloses a method for preparing a composite antibacterial agent, comprising the following steps:
[0081] Q1: 2.81 g of 3-phenyl-2-acryloyl chloride and 1.08 g of ethanolamine hydrochloride were added to a container filled with nitrogen and equipped with a condensing device, and then 0.012 g of hydroquinone was added, and the temperature was raised to 95°C for reaction for 2 hours, and stirred vigorously, and then the temperature was lowered to 75°C for reaction for 4 hours, and then cooled to 25°C, diluted with tetrahydrofuran, precipitated with n-pentane, washed with distilled water, dried, and recrystallized with a mixed solution of ethyl acetate and isopropanol in a volume ratio of 7:3, and dried to obtain monomer 1;
[0082] Q2: 1.6 g of monomer 1 and 2.3 g of butyl methacrylate were added to a container equipped with a magnetic stirrer, nitrogen was introduced, and then 19 mL of dimethyl sulfoxide was added, and the temperature was raised to 75°C. 0.06 g of azobisisobutyronitrile was dissolved in 4.5 mL of dimethyl sulfoxide and then slowly added dropwise to the container, and the reaction was carried out for 14 hours. The mixture was precipitated with acetone, washed, redissolved with dimethyl sulfoxide, precipitated again with acetone, washed, and dried at 45°C to obtain monomer 2;
[0083] Q3: 1.2 g of monomer 2, 3.6 g of trimethylamine and 1.87 g of 1H-pyrazole-1-carboximidamide hydrochloride were added to a container containing 60 mL of deionized water. After nitrogen was introduced, the mixture was reacted at room temperature for 24 h. After the reaction was completed, the mixture was dialyzed for 48 h using a dialysis bag with a molecular weight cutoff of 1000. The mixture was concentrated by rotary evaporation and freeze-dried to obtain a composite antibacterial agent.
[0084] This embodiment discloses a method for preparing a wear-resistant layer material, comprising the following steps:
[0085] S1: 12.37 g of 4-aminophenol, 23.49 g of 2-chloro-5-nitrotrifluorotoluene and 9.97 g of potassium carbonate were added to a container containing 60 mL of N,N-dimethylformamide, and the temperature was raised to 80°C for reaction for 12 h. After the reaction was completed, the temperature was lowered, distilled water was added, and the mixture was stirred. The crude product was collected and recrystallized from ethanol to obtain intermediate product 1; 1.997 g of 4-nitrobenzoyl chloride was added to a container containing 30 mL of tetrahydrofuran, and the mixture was stirred until completely dissolved. 1.973 g of pyridine was added dropwise and the reaction was carried out for 45 min. Then, 6.873 g of intermediate product 1 was dissolved in 30 mL of tetrahydrofuran and the mixture was slowly added dropwise to the container, and the mixture was stirred under an ice bath for 5 h. The mixture was heated to 80°C for reaction for 12 h, cooled, poured into distilled water, filtered, and recrystallized from N,N-dimethylformamide. The intermediate product 2 was filtered and obtained;
[0086] S2: Under nitrogen atmosphere, 5.67 g of intermediate product 2 was added to a container containing 170 mL of ethanol, stirred for 3 h, then 0.2 g of palladium activated carbon was added, the temperature was raised to 75 ° C for reaction for 2 h, then 32 mL of hydrazine hydrate was added dropwise, and the temperature was kept at 75 ° C for reflux reaction for 12 h. After the reaction was completed, the filtrate was collected by hot filtration and rotary evaporation to obtain a crude product, which was recrystallized from ethanol to obtain intermediate 3;
[0087] S3: Add 11g of intermediate 3 to a container containing 22mL of N,N-dimethylacetamide, stir to dissolve, then add 7.5g of 3,4,9,10-perylenetetracarboxylic dianhydride, stir, mix and react at room temperature for 12h under nitrogen environment, spread flat, heat at 85℃ for 5h, and heat to cure. The process is: react at 100℃ for 2h, react at 150℃ for 1h, react at 200℃ for 1h, react at 250℃ for 1h, react at 300℃ for 1h, cool, and obtain the wear-resistant layer material.
[0088] This embodiment discloses a method for preparing an antibacterial composite nonwoven fabric, comprising the following steps:
[0089] Step 1: 5 g of the composite antibacterial agent and 80 g of polyacrylic acid are mixed, and then electrospinned to obtain an antibacterial layer material;
[0090] Step 2: placing the spunbond nonwoven fabric between the antibacterial layer material and the wear-resistant layer material, preheating, hot pressing, cooling and shaping, and cutting to obtain the antibacterial composite nonwoven fabric.
[0091] Comparative Example 1: Compared with Example 1, in the process of preparing the composite antibacterial agent in Comparative Example 1, 3-phenyl-2-acryloyl chloride is not added, and other conditions remain unchanged.
[0092] Comparative Example 2: Compared with Example 1, in the process of preparing the wear-resistant layer material in Comparative Example 2, 3,4,9,10-perylenetetracarboxylic dianhydride is not added, and other conditions remain unchanged.
[0093] Comparative Example 3: Compared with Example 1, in Comparative Example 3, during the process of preparing the antibacterial composite non-woven fabric, no composite antibacterial agent is added, and other conditions remain unchanged.
[0094] Comparative Example 4: Compared with Example 1, in Comparative Example 4, during the process of preparing the antibacterial composite non-woven fabric, no wear-resistant layer material is added, and other conditions remain unchanged.
[0095] Experimental Example: The antibacterial composite nonwoven fabrics prepared in Examples 1-5 and Comparative Examples 1-4 were subjected to performance tests. The wear resistance of the samples was tested according to GB / T 20991-2007, the antibacterial performance of the samples was tested according to FZ / T 62015-2009, and the heat resistance of the samples was tested according to GB / T 13767-1992. The test results are shown in Table 1:
[0096] Table 1
[0097]
[0098] It can be seen from the test results in Table 1 that the antibacterial composite nonwoven fabrics prepared in Examples 1-5 of the present invention have excellent wear resistance, antibacterial performance and heat resistance. By comparing Comparative Example 1 with Examples 1-5, it can be seen that the addition of 3-phenyl-2-acryloyl chloride can effectively improve the antibacterial performance of the antibacterial composite nonwoven fabric; by comparing Comparative Example 2 with Examples 1-5, it can be seen that the addition of 3,4,9,10-perylenetetracarboxylic dianhydride can effectively improve the wear resistance and heat resistance of the antibacterial composite nonwoven fabric; by comparing Comparative Example 3 with Examples 1-5, it can be seen that the addition of a composite antibacterial agent can effectively improve the antibacterial performance of the antibacterial composite nonwoven fabric; by comparing Comparative Example 4 with Examples 1-5, it can be seen that the use of a wear-resistant layer material can effectively improve the wear resistance and heat resistance of the antibacterial composite nonwoven fabric.
[0099] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
[0100] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. An antibacterial composite nonwoven fabric, characterized in that: The invention comprises a wear-resistant layer, an inner lining layer and an antibacterial layer, wherein the inner lining layer is located between the wear-resistant layer and the antibacterial layer, and the layers are bonded by hot pressing. The antibacterial layer material is prepared from a composite antibacterial agent and polyacrylic acid, the inner lining layer material is composed of a spunbonded non-woven fabric, and the wear-resistant layer material is prepared from 4-aminophenol, 2-chloro-5-nitrotrifluorotoluene, 4-nitrobenzoyl chloride, hydrazine hydrate and 3,4,9,10-perylenetetracarboxylic dianhydride.
2. The antibacterial composite nonwoven fabric according to claim 1, characterized in that: The preparation method of the composite antibacterial agent comprises the following steps: Q1: 3-phenyl-2-acryloyl chloride and ethanolamine hydrochloride are added to a container filled with nitrogen and equipped with a condensing device, and then hydroquinone is added, the temperature is raised to react, vigorously stirred, then the temperature is lowered to react, cooled, diluted, precipitated, washed, dried, recrystallized, and dried to obtain monomer 1; Q2: Monomer 1 and butyl methacrylate are added to a container equipped with a magnetic stirrer, nitrogen is introduced, dimethyl sulfoxide is added, the temperature is raised, azobisisobutyronitrile is dissolved in dimethyl sulfoxide and then slowly added dropwise to the container, react, precipitate, wash, redissolve, precipitate, wash, and dry to obtain monomer 2; Q3: Add monomer 2, trimethylamine and 1H-pyrazole-1-carboximidamide hydrochloride to a container containing deionized water, introduce nitrogen, and react at room temperature. After the reaction is completed, dialyze, concentrate by rotary evaporation, and freeze-dry to obtain a composite antibacterial agent.
3. The antibacterial composite nonwoven fabric according to claim 2, characterized in that: In the Q1, the molar ratio of 3-phenyl-2-acryloyl chloride and ethanolamine hydrochloride is (3-3.5): (2-2.3), the heating reaction temperature is 90-95°C, the reaction time is 1-2h, the cooling reaction temperature is 70-75°C, the reaction time is 2-4h, and the mixture is cooled to 25-30°C, diluted with tetrahydrofuran, precipitated with n-pentane, washed with distilled water, and recrystallized with a mixed solution of ethyl acetate and isopropanol in a volume ratio of 7:
3.
4. The antibacterial composite nonwoven fabric according to claim 2, characterized in that: In the Q2, the amount ratio of monomer 1, butyl methacrylate, dimethyl sulfoxide, azobisisobutyronitrile and dimethyl sulfoxide in which azobisisobutyronitrile is dissolved is (1-1.8) g: (2-2.4) g: (15-20) mL: (0.04-0.07) g: (3-5) mL, the heating temperature is 70-75° C., the reaction time is 12-16 h, precipitated with acetone, washed, redissolved with dimethyl sulfoxide, precipitated with acetone again, washed, and the drying temperature is 40-45° C.; in the Q3, the amount ratio of monomer 2, trimethylamine and 1H-pyrazole-1-carboxamidine hydrochloride is (1-1.3) g: (3-3.8) g: (1.5-1.95) g, the reaction time at room temperature is 20-24 h, the molecular weight cutoff of the dialysis bag is 1000, and the dialysis time is 48-56 h.
5. The antibacterial composite nonwoven fabric according to claim 1, characterized in that: The preparation method of the wear-resistant layer material comprises the following steps: S1: Add 4-aminophenol, 2-chloro-5-nitrotrifluorotoluene and potassium carbonate to a container filled with N,N-dimethylformamide, heat up to react, cool down after the reaction, add distilled water, stir, collect the crude product, recrystallize, and obtain intermediate product 1; add 4-nitrobenzoyl chloride to a container filled with tetrahydrofuran, stir until completely dissolved, drop pyridine, react, then dissolve intermediate product 1 in tetrahydrofuran and slowly drop it into the container, stir under ice bath, heat up to react, cool, pour into distilled water, filter, recrystallize, filter to obtain intermediate product 2; S2: Under nitrogen atmosphere, add intermediate product 2 to a container filled with ethanol, stir, then add palladium activated carbon, heat to react, then add hydrazine hydrate dropwise, keep warm and reflux to react, after the reaction is completed, filter and collect the filtrate while hot, rotary evaporate to obtain a crude product, and recrystallize to obtain intermediate 3; S3: Add the intermediate 3 to a container containing N,N-dimethylacetamide, stir and dissolve, then add 3,4,9,10-perylenetetracarboxylic dianhydride, stir, mix and react at room temperature under a nitrogen environment, spread, heat, heat and cure, and cool to obtain a wear-resistant layer material.
6. The antibacterial composite nonwoven fabric according to claim 5, characterized in that: In the S1, the molar ratio of 4-aminophenol, 2-chloro-5-nitrotrifluorotoluene and potassium carbonate is (0.09-0.12): (0.09-0.11): (0.068-0.073), the temperature of the reaction is 80-90°C, the reaction time is 10-12h, and recrystallization is performed using ethanol; the molar ratio of 4-nitrobenzoyl chloride, pyridine and intermediate 1 is (0.01-0.015): (0.018-0.026): (0.017-0.025), the reaction time is 30-45min, the stirring time under ice bath is 3-5h, the temperature of the reaction is 60-80°C, the time is 10-12h, and recrystallization is performed using N,N-dimethylformamide.
7. The antibacterial composite nonwoven fabric according to claim 5, characterized in that: In S2, the dosage ratio of the intermediate product 2, ethanol, palladium activated carbon and hydrazine hydrate is (4.47-5.82) g: (150-175) mL: (0.18-0.21) g: (25-35) mL, the stirring time is 2-4 h, the heating reaction temperature is 70-75°C, the reaction time is 1-2 h, the insulation reflux reaction temperature is 70-75°C, the reaction time is 12-14 h, and recrystallization is carried out with ethanol.
8. The antibacterial composite nonwoven fabric according to claim 5, characterized in that: In S3, the usage ratio of intermediate 3, N,N-dimethylacetamide and 3,4,9,10-perylenetetracarboxylic dianhydride is (8-12) g: (15-25) mL: (6-8) g, the mixing reaction time at room temperature is 10-14 h, the heating temperature is 80-85°C, the time is 5-7 h, and the temperature rise curing process is: reaction at 100°C for 2 h, reaction at 150°C for 1 h, reaction at 200°C for 1 h, reaction at 250°C for 1 h, and reaction at 300°C for 1 h.
9. The method for preparing the antibacterial composite nonwoven fabric according to any one of claims 1 to 8, characterized in that: The following steps are involved: Step 1: Mix the composite antibacterial agent and polyacrylic acid, and then perform electrospinning to obtain an antibacterial layer material; Step 2: placing the spunbond nonwoven fabric between the antibacterial layer material and the wear-resistant layer material, preheating, hot pressing, cooling and shaping, and cutting to obtain the antibacterial composite nonwoven fabric.
10. The method for preparing the antibacterial composite nonwoven fabric according to claim 9, characterized in that: In the step 1, the usage ratio of the composite antibacterial agent and the polyacrylic acid is (3-6) g: (60-90) g.
Citation Information
Patent Citations
Antibacterial composite non-woven fabric
CN105398152A
Polyimide
CA2028358A1
Method for preparing polyimide film from pyromellitic dianhydride
CN108102096A
Nano drug of photoinduced release of nitric oxide anti-biofilm, and preparation and application method
CN113274495A
Cationic perylene diimide antibacterial agent, preparation method thereof and antibacterial cotton fabric
CN118373821A